(N{EDEWERY EWROPEJSKIH HUDOVNIKOW(B.s - (No(B.(Nw(B.(NmOROZOWA(B.s ((NmOSKWAs (NaBRISs, 2019)
(NuWROPEJSKIE HUDOVNIKI NA PROTAVENII MNOGIH WEKOW DERVALI PAL_MU PERWENSTWA W OBLASTI IZOBRAZITEL_NOGO ISKUSSTWA(B.s